Structural insights into the broad-spectrum antiviral target endoplasmic reticulum alpha-glucosidase II - Zitzmann, N; Caputo, AT; Alonzi, DS; Kiappes, JL; Struwe, WB; Cross, A; Basu, S; Darlot, B; Roversi, P (Springer, 2018)
Targeting the host-cell endoplasmic reticulum quality control (ERQC) pathway is an effective broad-spectrum antiviral strategy. The two ER resident α-glucosidases whose sequential action permits entry in this pathway are the targets of glucomimetic inhibitors. Knowledge of the molecular details of the ER α-glucosidase II (α-Glu II) structure was limited. We determined crystal structures of a trypsinolytic fragment of murine α-Glu II, alone and in complex with key catalytic cycle ligands, and four different broad-spectrum antiviral iminosugar inhibitors, two of which are currently in clinical trials against dengue fever. The structures highlight novel portions of the enzyme outside its catalytic pocket which contribute to its activity and substrate specificity. These crystal structures and hydrogen-deuterium exchange mass spectrometry of the murine ER alpha glucosidase II heterodimer uncover the quaternary arrangement of the enzyme’s α- and β-subunits, and suggest a conformational rearrangement of ER α-Glu II upon association of the enzyme with client glycoproteins.